Characterization of TtALV2, an Essential Charged Repeat Motif Protein of the Tetrahymena thermophila Membrane Skeleton - El-Haddad, Houda (American Society for Microbiology, 2013)
Alveolins are a recently described class of proteins common to all members of the superphylum Alveolata that are characterized by conserved charged repeat motifs (CRMs) but whose exact function remains unknown. We have analyzed the smaller of the two alveolins of Tetrahymena thermophila, TtALV2. The protein localizes to dispersed, broken patches arranged between the rows of the longitudinal microtubules. Macronuclear knockdown of Ttalv2 leads to multinuclear cells with no apparent cell polarity and randomly occurring cell protrusions, either by interrupting pellicle integrity or by disturbing cytokinesis. Correct association of TtALV2 with the alveoli or the pellicle is complex and depends on both the termini as well as the charged repeat motifs of the protein. Proteins containing similar CRMs are a dominant part of the ciliate membrane cytoskeleton, suggesting that these motifs may play a more general role in mediating membrane attachment and/or cytoskeletal association. To better understand their integration into the cytoskeleton, we localized a range of CRM-based fusion proteins, which suggested there is an inherent tendency for proteins with CRMs to be located in the peripheral cytoskeleton, some nucleating as filaments at the basal bodies. Even a synthetic protein, mimicking the charge and repeat pattern of these proteins, directed a reporter protein to a variety of peripheral cytoskeletal structures in Tetrahymena. These motifs might provide a blueprint for membrane and cytoskeleton affiliation in the complex pellicles of Alveolata.